Penerapan Akuntansi Usaha Kecil Dan Menengah : Studi Kasus Pada Bandrek Sahib - Reza Hanafi Lubis; Rizqy Fadhlina Putri; Muhammad Rizaldy Wibowo; Silvi Dwi Ningrum; Arifah Zahirani (JURNAL AKUNTANSI AUDIT DAN PERPAJAKAN INDONESIA (JAAPI), 2026)
This study aims to analyze the application of accounting in Micro, Small, and Medium Enterprises (MSMEs) and to identify the gaps between current practices and the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). A case study was conducted at Bandrek Sahib, a culinary MSME located in Medan City that has been operating since 2000. The research employed a qualitative method with a case study approach through in-depth interviews, direct observation, and documentation. The results show that the accounting application at Bandrek Sahib remains very simple, limited to manual recording of cash inflows and outflows, and fails to separate personal finances from business finances. Bandrek Sahib has not prepared the three required financial statement components mandated by SAK EMKM, namely the Income Statement, Statement of Financial Position (Balance Sheet), and Notes to the Financial Statements. The contributing factors to this gap include the owner's limited accounting knowledge and understanding, minimal socialization and assistance from relevant parties, and limited resources for bookkeeping management. The study concludes that Bandrek Sahib's accounting practices do not comply with SAK EMKM, resulting in poor quality of financial information and obstacles in accessing financing. This research recommends improving accounting literacy, intensifying SAK EMKM socialization, and providing ongoing assistance for MSMEs.